2021
DOI: 10.1002/ccr3.4214
|View full text |Cite
|
Sign up to set email alerts
|

Primary squamous cell carcinoma of the breast in a young female‐ A rare ailment

Abstract: Primary squamous cell carcinoma of the breast is an extremely rare invasive breast carcinoma with rapid progression and worse prognosis. Careful assessment and diagnosis of the entity should also be considered in a rapidly progressing breast tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Our contribution to this sparse body of literature is the presentation of an 80-year-old woman diagnosed with an early-stage pT1 PSCC of the breast who was treated with BCT -a clinical decision that is notably rare in this context. Beyond the SEER data, the literature documents only nine instances of adjuvant radiotherapy following PSCC, with merely four of these cases opting for breast conservation therapy, as summarized in Table 1 [7][8][9][10]. This case underscores the underexplored demographic and clinical pathways for managing early-stage PSCC with BCT and adjuvant radiotherapy.…”
Section: Discussionmentioning
confidence: 97%
“…Our contribution to this sparse body of literature is the presentation of an 80-year-old woman diagnosed with an early-stage pT1 PSCC of the breast who was treated with BCT -a clinical decision that is notably rare in this context. Beyond the SEER data, the literature documents only nine instances of adjuvant radiotherapy following PSCC, with merely four of these cases opting for breast conservation therapy, as summarized in Table 1 [7][8][9][10]. This case underscores the underexplored demographic and clinical pathways for managing early-stage PSCC with BCT and adjuvant radiotherapy.…”
Section: Discussionmentioning
confidence: 97%
“…Although the patient did not complete the course of neoadjuvant chemotherapy, evaluation of pathologic responses after the neoadjuvant chemotherapy has achieved a good therapeutic effect. In this way, Shrestha et al (22) reported a patient with large breast squamous cell carcinoma treated with a TP regimen and achieved long- term disease-free survival. Thus, it can be seen that the TP regimen might be effective for MSCCB.…”
Section: Discussionmentioning
confidence: 99%
“…Primary squamous cell carcinoma (PSCC) of the breast is a very rare subtype of saprophytic carcinoma; it accounts for approximately 0.06%-0.2% of all breast cancers (Chen et al, 2022;Wu et al, 2022). PSCC has large tumors, rapid progression, frequent recurrence, and high mortality (Anne et al, 2019;Shrestha et al, 2021). Surgery and radiotherapy can effectively control low-grade squamous cell carcinoma locally (Qi et al, 2021;Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%